2017
DOI: 10.1007/s00345-017-2056-y
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave lithotripsy: techniques for improving outcomes

Abstract: While single-treatment success rates may not equal those of ureteroscopy or percutaneous nephrolithotomy, with proper patient selection, optimization of SWL technique, and use of adjunctive treatment after SWL, success rates can be maximized while further reducing the already low rate of serious complications. SWL remains an excellent treatment option for calculi even in 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…[20] Recently, vasoconstriction has been reported to occur without a pause. [21] In our study, the stepwise voltage ramping technique, low frequency, and US guidance gave us acceptable results.…”
Section: Discussionmentioning
confidence: 67%
“…[20] Recently, vasoconstriction has been reported to occur without a pause. [21] In our study, the stepwise voltage ramping technique, low frequency, and US guidance gave us acceptable results.…”
Section: Discussionmentioning
confidence: 67%
“…To maximize the e cacy and outcomes while minimizing complications of SWL, certain options regarding patient and stone characteristics have been proposed [16]. Obese patients and those with a higher body mass index (BMI) may have a larger skin to stone distance revealed during clinical examination, which could lead to unfavorable SWL success rates [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary studies have shown that the success rate of SWL for renal stones ranges from 47 to 92% [2][3][4][5][6][7]. This highly variable result is due to various crucial factors, including stone composition and size [8][9][10][11], skin to stone distance [12], lithotripter energy power [13] and frequency [14,15], patient positioning [16], and patient tolerance and respiration [16,17]. Less than half of the administered shockwaves may be accurately focused on the targeted calculus [18], and the excessive energy and shockwaves can cause damage to the parenchyma and adjacent organs.…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the efficacy and outcomes while minimizing complications of SWL, certain options regarding patient and stone characteristics have been proposed [16]. Obese patients and those with a higher body mass index (BMI) may have a larger skin to stone distance revealed during clinical examination, which could lead to unfavorable SWL success rates [12,23].…”
Section: Discussionmentioning
confidence: 99%